The Effect Of Marine Fouling And Seawater Corrosion On Doped Titanium Nitride Electrode - Muhammad Sabri, Muhammad Iman Rif’at (Universiti Sains Malaysia, 2022)
Seawater corrosion is no longer common in daily living routine or life, as it is a natural process that cause severe failure problems as well as inducing marine fouling which has been affecting the worldwide including Malaysia naval ships, vassals and marine applications in seawater as one of the biggest contributors to this concern matters. Hence sacrificial anode cathodic protection is selected to overcome the problems. This research studies the effectiveness of doped titanium nitride electrode in simulating the marine application in the seawater environment. By using specific seawater, pH, immersion testing, linear polarization and electrochemical impedance spectroscopy (EIS) are the test conducted to obtain the data. The sintered doped titanium nitride electrode that is used with seaweed shows the highest weight gain, which is 1.66g for immersion testing. Using regression analysis to design experiment for both linear polarization and electrochemical impedance spectroscopy. For linear polarization, the 3 parameters chosen are immersion days, type of seawater and type of fouling. The highest corrosion rate is 2.715 mm/year which come from nine days of immersion, Ban Pecah seawater and cockles which was expected to give significant effect on corrosion rate. Whereas the lowest corrosion rate is 0.48041 mm/years come from 3 days of immersion, Batu Ferringhi seawater and seaweed. From EIS, two parameter that being considered are pH and immersion days. It can be observed that the lowest bulk capacitance is 0.9971μF which come from 6.5ph and nine days. Whereas the highest bulk resistance is 0.98969 μF for 7.5ph and six days of immersion.